A New Historicist Vein in British Romanticism - Datta, Vijay Kumar; Pandey, Beerendra (Journal of Advanced Academic Research, 2018)
The Romanticism the was the very important period after the Shakespearian time/ Elizabethan period was full of trauma and guilt as well as commodification. The poems and other genres of literature attempted about that time and critics explain about the literary atmosphere. After 1960s, a new trend in literature got entrance that has made the miracle in this field that is quite scientific.